Enhancing water levels of degraded, bare, tropical peatland in West Kalimantan, Indonesia: Impacts on CO2 emission from soil respiration - DWI ASTIANI; BURHANUDDIN BURHANUDDIN; EVI GUSMAYANTI; TRI WIDIASTUTI; MUHAMMAD J. TAHERZADEH (Biodiversitas Journal of Biological Diversity, 2018)
Astiani D, Burhanuddin, Gusmayanti E, Widiastuti T, Taherzadeh MJ. 2018. Enhancing water levels of degraded, bare, tropical peatland in West Kalimantan, Indonesia: Impacts on CO2 emission from soil respiration. Biodiversitas 19: 522-527. The major drivers of deforestation in West Kalimantan have been the development for large or small-scale expansion of agricultural activities; the establishment of oil palm and other plantations; fire; and degradation of forests particularly from industrial logging. Our previous research findings have shown that such activities in affected peatland areas have lowered the water table levels (down to 0.5-1.0 m depths), and have significantly increased CO2 emissions from the peat soils. It has been demonstrated that unmanaged, lowered water tables in peatlands act as one of the main factors inflating soil carbon emissions - an issue that has assumed global significance in recent decades. Regulating peatland water tables has the potential to mitigate degraded peatland carbon emissions as well as improve the hydrological functions for communities who farm the peatlands. However, we are still uncertain exactly how much impact controlled raising of the peatlands water tables will have on reducing soil CO2 emissions. The research described here aimed to mitigate CO2 emissions by raising and regulating water levels on drained peatland to restore and enhance its hydrological functions. The results confirmed that raising the water table significantly decreases CO2 emissions and improves water availability and management for crop production in the coastal peatland of Kubu Raya district, West Kalimantan. Water levels previously at 60cm below the soil surface were regulated to raise the watertable up to just 30 cm below the surface and this reduced peatland carbon emissions by about 49%. However, longer-term monitoring is required to ensure that the hydrological benefits and CO2 mitigation can be sustained.